NEW HIGH-RESOLUTION SHALLOW-DEPTH MULTI-ELECTRODE DEVICE FOR ELECTRICAL RESISTIVITY TOMOGRAPHY - Khomenko, R.; Bondar, K.; Popov, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The new multi-electrode device for high-resolution electrical resistivity tomography is designed. Two lines with 32 electrodes each are connected to the device. Electrodes can be placed at a distance of 0.5-1 m from each other, the maximum deep implication is limited at approximately 11 meters. The parameters of the device and examples of practical use for studying of near-surface structure are represented in the article.